2007
DOI: 10.1152/ajpgi.00134.2006
|View full text |Cite
|
Sign up to set email alerts
|

Short-form Ron receptor is required for normal IFN-γ production in concanavalin A-induced acute liver injury

Abstract: Abrogation of Ron receptor tyrosine kinase function results in defects in macrophage activation and dysregulated acute inflammatory responses in vivo. Several naturally occurring constitutively active alternative forms of Ron have been identified, including from primary human tumors and tumor cell lines. One of these alternative forms, short-form (SF) Ron, is generated from an alternative start site in intron 10 of the Ron gene that eliminates most of the extracellular portion of the receptor and is overexpres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 30 publications
0
16
1
Order By: Relevance
“…Therefore, the appearance of IL-10 increase is indicative of hepatocyte recovery. Recently, the treatment of LPS plus PEA, LPS alone, or Con-A resulted in a significant increase in INF-γ in mouse study [4,25]. In our study, a trace amount of INF-γ was detected, but not dose or time dependent, though.…”
Section: Discussioncontrasting
confidence: 47%
“…Therefore, the appearance of IL-10 increase is indicative of hepatocyte recovery. Recently, the treatment of LPS plus PEA, LPS alone, or Con-A resulted in a significant increase in INF-γ in mouse study [4,25]. In our study, a trace amount of INF-γ was detected, but not dose or time dependent, though.…”
Section: Discussioncontrasting
confidence: 47%
“…The gene encoding Ron contains an internal promoter that drives expression of an N-terminally truncated form of Ron that lacks the extracellular ligand binding domain but retains the transmembrane and kinase domains (Sf-Ron). The inflammatory defects observed in mice harboring an Sf-Ron–specific deletion support the concept that, like the full-length RON receptor, Sf-Ron also plays a critical role in the regulation of macrophage activation (30). To determine whether LPS regulates the expression of Ron and/or Sf-Ron in macrophages, we stimulated primary peritoneal macrophages with LPS and examined Ron and Sf-Ron expression by real-time PCR (Fig.…”
Section: Resultsmentioning
confidence: 65%
“…Recent studies have also suggested that SF-Ron has nonredundant biological functions relative to full-length Ron in the progression of inflammatory immune responses in vivo. These observations suggest that the function of SF-Ron is biologically distinct from that of the fulllength receptor and may participate in tumorigenesis [25].…”
Section: Variant Forms Of the Ron Receptormentioning
confidence: 96%
“…Variants of Ron have been identified in both normal and malignant tissues. In mice, short-form (SF-)Ron is naturally expressed in select cells and tissues including expression in the spleen and in splenic T cells, bone marrow, testes, lung, ovary, peritoneal macrophages, and in several hematopoietic cells including stem cells [24,25]. SF-Ron is generated from an alternative start site located in intron 10 of the Ron gene and generates a Ron protein containing only a small extracellular portion along with the transmembrane and intracellular domains.…”
Section: Variant Forms Of the Ron Receptormentioning
confidence: 99%
See 1 more Smart Citation